GEOPOLITICAL RISKS AS A DRIVER OF THE TRANSFORMATION OF THE INTERNATIONAL MARKETING ENVIRONMENT (INNOVATIVE ECONOMY, 2026)
Bratko O.S., Myhal O.F. GEOPOLITICAL RISKS AS A DRIVER OF THE TRANSFORMATION OF THE INTERNATIONAL MARKETING ENVIRONMENTPurpose. The aim of the article is to conduct a comprehensive analysis of the impact of geopolitical risks on the functioning of the international marketing environment and to identify key directions for companies’ strategic adaptation in conditions of increasing global instability.Methodology of research. A set of general scientific and specific research methods was used to achieve the stated objective: analysis and synthesis – to generalize theoretical approaches to the interpretation of geopolitical risks; a systemic approach – to consider the international marketing environment as a complex multi-level system; comparative analysis – to assess the impact of different types of geopolitical risks; structural and logical method – to develop conceptual models of risk transmission channels; tabular and graphical methods – to visualize the typology of risks and directions of companies’ strategic adaptation.Findings. The article substantiates that geopolitical risks are becoming systemic in nature and act as a key factor in the transformation of the international marketing environment. The main types of geopolitical risks are systematized and their marketing implications are identified. Key transmission channels – trade, investment, logistics, energy, and regulatory – through which geopolitical instability transforms into changes in market conditions are distinguished. It is established that under the influence of geopolitical shocks, supply chains are reconfigured, demand structures change, markets become more regionalized, and companies’ marketing strategies are transformed.Originality. Within the framework of this study, a comprehensive analysis of the impact of geopolitical risks on international marketing in the context of the transformation of the global economic environment was conducted for the first time. Particular attention was paid to the study of geopolitical risks as a system-forming factor of the international marketing environment, the generalization of their typology taking into account marketing effects, as well as the identification of the main channels of their influence on the activities of international companies. The necessity of transitioning from a model of global standardization to adaptive marketing strategies under conditions of increasing geopolitical instability and fragmentation of global markets was substantiated.Practical value. The obtained results can be used by enterprises engaged in foreign economic activity to improve marketing strategies, particularly in terms of market diversification, product and communication adaptation, supply chain management, and compliance with regulatory requirements. In addition, the results of the study may be useful for public authorities and economic policy institutions in developing support measures for export-oriented businesses under conditions of geopolitical instability.Key words: geopolitical risks, international marketing, globalization, regionalization, supply chains, marketing environment, strategic adaptation.
Keywords: geopolitical risks; international marketing; globalization; regionalization; supply chains; marketing environment; strategic adaptation